Description of five new eulophid species (Hymenoptera: Eulophidae) associated with leaf vein galls of Madhuca longifolia (J. Koenig) (Sapotaceae) in India - Singh, Sudhir; Kumar, Arvind; Kaneria, Manish (Zootaxa, 2022)
Five species of eulophids were reared from the leaf vein galls of Madhuca longifolia (Koenig) (Sapotaceae), which is a multipurpose tree in the tropical forests of India. Surveys from 2015 to 2018 in the states of Jharkhand, Chhattisgarh and Uttarakhand revealed that M. longifolia were heavily galled. Rearing of galls during 2015–16 resulted in emergence of only one species of Selitrichodes (Hymenoptera: Eulophidae), but in subsequent rearings during 2017 to 2018 an additional 4 eulophid species were found to be associated with these galls. Two species belonged to genus Aprostocetus Westwood, one to genus Quadrastichus Girault and one to Chrysonotomyia Ashmead. All five species—Selitrichodes madhucae Singh & Kaneria sp. nov., Aprostocetus madhucae Singh sp. nov., A. dehradunensis Singh sp. nov., Quadrastichus manmohani Singh sp. nov. and Chrysonotomyia madhucae Singh sp. nov. are new to science and described from both female and male specimens. Some observations on their biology are also given.